DEVELOPMENT AND VALIDATION OF INTERVIEW GUIDELINES FOR NEED ASSESSMENT UTILIZATION OF INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) IN ELEMENTARY SCHOOL - Aka, Kukuh Andri (EDUTECH, 2018)
The purpose of this study was to develop structured interview guideline instruments for the use of technology facilities in primary schools which included aspects of (1) ICT concept, (2) types of sources and media of ICT-based learning in primary schools, (3) forms of use of ICTs by elementary teacher and students, and (4) efforts to increase ICT mastery by elementary school teachers. To achieve these objectives, activities are carried out including: (1) formulating the theoretical aspects of the learning plan developed; (2) compiling the interview guideline instrument; (3) arranging interview guide questions; (4) conducting expert judgment; (5) revision and improvement of instruments. Based on the results of the research and discussion, it can be concluded that according to the content validation by instrument experts can be said to have good categories, and can be used.